Boy posed with Styrofoam ball and baseball bat - Dow Chemical Company (1966)
General view of a young boy posed with a ball and baseball bat made out of Styrofoam. Invented in 1941 by researchers in Dow's Chemical Physics Lab, "Styrofoam" properly refers to the Dow Chemical Company’s trademarked brand of closed-cell extruded polystyrene foam commonly used for thermal insulation and craft applications.
Keywords: Foamed materials; Dow Chemical Company; Foam; Children; Polystyrene